A LEXICAL-SEMANTIC ANALYSIS OF SYNONYMIC RELATIONS IN THE UZBEK LANGUAGE (KONFERENSIYA, 2026)
This article explores synonymic relations in the Uzbek language from a lexical-semantic perspective. Synonyms are considered an essential component of the lexical system, contributing to semantic precision and stylistic diversity in speech. The study examines the types, semantic nuances, and functional characteristics of Uzbek lexical synonyms. The findings demonstrate that synonymic relations play a crucial role in enriching vocabulary and enhancing communicative effectiveness.